Business Strategy Development for HAWS Home Accessories - Dina Rachman, Farah; Anggoro, Yudo (The Indonesian Journal of Business Administration, 2017)
Abstract - Haws is a new-comers in home dÃ©cor industry. The company started to enter the competition in the middle of 2015. As a new entrant in the industry, the company realizes the competition in the industries is very high, moreover the new entrants keep increasing due to the low barrier entry. Haws sales not increase significantly as targeted and the company realize they need strategy to challenge the competition. Thus, the purpose of this research is to develop business strategy for Haws. This research is using the combination of qualitative by interviews with related parties, and quantitative method by distributing questionnaire to know the importance level of variables in buying home dÃ©cor product and the performance of Haws. The result shows 10 variables, which are design, service, product quality, price, delivery time, how to order, product availability, packaging, brand, and product choices that has significant effect for customers. Those variables will be interpreted using Diamond strategy. The final results of the research shows, Haws needs to maintain and improve the custom service, because it is as their value from competitors. Haws should maintain the price and develop the quality in order to preserve their customers with greater value benefits. To make sure a good service to the customer, Haws can make a customer feedback form to know about their performance and able to improve based on what customer wants, and hire new staff to handle the service in the future. Make a SOP for production is needed, so the product will be distribute and deliver to customer appropriate with the time estimated. In terms of adding new products can be done by doing collaboration with other brands because it can grab the market, lower cost, and also lower risk. After having many variety of products, Haws can make a website so customer have another alternative to put the order. At the end, more aggressive promotion including marketing activation should be done, so people will more aware about Haws.Keywords: Home decor business, business strategy, Diamond Strategy